A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Intragroup competition predicts individual foraging specialisation in a group‐living mammal - Catherine E. Sheppard; Richard Inger; Robbie A. McDonald; Sam Barker; Andrew L. Jackson; Faye J. Thompson; Emma I. K. Vitikainen; Michael A. Cant; Harry H. Marshall (Ecology Letters, 2018)
Individual foraging specialisation has important ecological implications, but its causes in group‐living species are unclear. One of the major consequences of group living is increased intragroup competition for resources. Foraging theory predicts that with increased competition, individuals should add new prey items to their diet, widening their foraging niche (‘optimal foraging hypothesis’). However, classic competition theory suggests the opposite: that increased competition leads to niche partitioning and greater individual foraging specialisation (‘niche partitioning hypothesis’). We tested these opposing predictions in wild, group‐living banded mongooses ( Mungos mungo ), using stable isotope analysis of banded mongoose whiskers to quantify individual and group foraging niche. Individual foraging niche size declined with increasing group size, despite all groups having a similar overall niche size. Our findings support the prediction that competition promotes niche partitioning within social groups and suggest that individual foraging specialisation may play an important role in the formation of stable social groupings.

Ocean acidification has little effect on developmental thermal windows of echinoderms from Antarctica to the tropics - Sam E. Karelitz; Sven Uthicke; Shawna A. Foo; Mike F. Barker; Maria Byrne; Danilo Pecorino; Miles D. Lamare (Global Change Biology, 2017)
As the ocean warms, thermal tolerance of developmental stages may be a key driver of changes in the geographical distributions and abundance of marine invertebrates. Additional stressors such as ocean acidification may influence developmental thermal windows and are therefore important considerations for predicting distributions of species under climate change scenarios. The effects of reduced seawater pH on the thermal windows of fertilization, embryology and larval morphology were examined using five echinoderm species: two polar ( Sterechinus neumayeri and Odontaster validus ), two temperate ( Fellaster zelandiae and Patiriella regularis ) and one tropical ( Arachnoides placenta ). Responses were examined across 12–13 temperatures ranging from −1.1 °C to 5.7 °C ( S. neumayeri ), −0.5 °C to 10.7 °C ( O. validus ), 5.8 °C to 27 °C ( F. zelandiae ), 6.0 °C to 27.1 °C ( P. regularis ) and 13.9 °C to 34.8 °C ( A. placenta ) under present‐day and near‐future (2100+) ocean acidification conditions (‐0.3 pH units) and for three important early developmental stages 1) fertilization, 2) embryo (prehatching) and 3) larval development. Thermal windows for fertilization were broad and were not influenced by a pH decrease. Embryological development was less thermotolerant. For O. validus , P. regularis and A. placenta , low pH reduced normal development, albeit with no effect on thermal windows. Larval development in all five species was affected by both temperature and pH ; however, thermal tolerance was not reduced by pH . Results of this study suggest that in terms of fertilization and development, temperature will remain as the most important factor influencing species' latitudinal distributions as the ocean continues to warm and decrease in pH , and that there is little evidence of a synergistic effect of temperature and ocean acidification on the thermal control of species ranges.

Contributions of genetic and environmental variance in early development of the Antarctic sea urchin Sterechinus neumayeri in response to increased ocean temperature and acidification - Shawna A. Foo; Kate M. Sparks; Sven Uthicke; Sam Karelitz; Mike Barker; Maria Byrne; Miles Lamare (Marine Biology, 2016)